Critical knowledge gaps and research needs related to the environmental dimensions of antibiotic resistance. (August 2018) - Larsson, D.G. Joakim; Andremont, Antoine; Bengtsson-Palme, Johan; Brandt, Kristian Koefoed; de Roda Husman, Ana Maria; Fagerstedt, Patriq; Fick, Jerker; Flach, Carl-Fredrik; Gaze, William H.; Kuroda, Makoto; Kvint, Kristian; Laxminarayan, Ramanan; et al.
Abstract: There is growing understanding that the environment plays an important role both in the transmission of antibiotic resistant pathogens and in their evolution. Accordingly, researchers and stakeholders world-wide seek to further explore the mechanisms and drivers involved, quantify risks and identify suitable interventions. There is a clear value in establishing research needs and coordinating efforts within and across nations in order to best tackle this global challenge. At an international workshop in late September 2017, scientists from 14 countries with expertise on the environmental dimensions of antibiotic resistance gathered to define critical knowledge gaps. Four key areas were identified where research is urgently needed: 1) the relative contributions of different sources of antibiotics and antibiotic resistant bacteria into the environment; 2) the role of the environment, and particularly anthropogenic inputs, in the evolution of resistance; 3) the overall human and animal health impacts caused by exposure to environmental resistant bacteria; and 4) the efficacy and feasibility of different technological, social, economic and behavioral interventions to mitigate environmental antibiotic resistance. 1 Highlights: The environment plays important roles in the development of antibiotic resistance. Critical knowledge gaps and research needs in this area were identified. These include aspects on evolution, transmission and interventions. The analysis provided may be useful for guiding future research efforts.